746 Delayed Rhythm Is Associated with Enhanced Discrimination for Negative Emotional Information. (3rd May 2021) - Chen, Ivy; Neikrug, Ariel; Adams, Joren; McMillan, Liv; Mander, Bryce; Yassa, Michael; Benca, Ruth
Abstract: Introduction: Mnemonic discrimination, the ability to differentiate novel and highly similar but not identical stimuli, is negatively associated with sleep deprivation and depression. Depression is additionally associated with increased discrimination specifically for negative emotional stimuli. While sleep and circadian activity rhythm (CAR) disturbances are common in depression and have been reported to have negative impact on hippocampal-dependent memories, their relationship with emotional discrimination has yet to be investigated. Methods: As part of a larger study, 14 patients with DSM-5 major depressive disorder (22.9±4.1 years, 71.4% female) and 13 healthy controls (29.4±8.5 years, 61.5% female) were evaluated with wrist-actigraphy (7–14 days) and completed an emotional discrimination task. Lure discrimination index (LDI) for each emotion type (i.e., negative, neutral, and positive) was calculated to indicate how well participants discriminated among highly similar lures. Actigraphy-derived sleep parameters included total sleep time (TST), sleep efficiency (SE), and midsleep time. Minute-by-minute actigraphy-derived activity counts were used to characterize CAR and parametrized using cosinor analysis and Generalized Additive Models (GAM) deriving the rhythm Acrophase, Amplitude, UP time, and DOWN time. A repeated measures ANOVA (within-subjects: emotion, between-subjects: group) assessed whether mnemonic discrimination differed between patients with MDD and controls. Partial correlations examined the association between sleep and CAR parameters with mnemonic discrimination, while controlling for age, state anxiety, depression severity, TST, and groups. Results: We found a significant effect of emotion [F(2, 90)=3.25, p=0.043], where neutral information was remembered better than emotional information (p's<0.005); no significant effect of group (MDD vs. control) was observed. Midsleep time and Acrophase were each positively associated with negative LDI (r=0.576, p=0.008; r=0.540, p=0.014, respectively). Exploratory GAM results suggested a significant positive correlation between UP time and negative LDI (r=0.497, p=0.022). TST, SE, Amplitude or DOWN time was not associated with LDIs. Conclusion: Delayed CAR, characterized by latter midsleep time and delayed acrophase and peak time of the morning activity, is associated with increased discrimination for negative emotional information, independent of depressive symptom severity. Future studies are needed to replicate these findings and further explore the potential cognitive benefits of adjunctive interventions addressing sleep/CAR in mitigating symptoms of depression. Support (if any): National Institutes of Health R01 432MH102392.